Investigation into the safety, and serological responses elicited by delivery of live intranasal vaccines for bovine herpes virus type 1, bovine respiratory syncytial virus, and parainfluenza type 3 in pre-weaned calves - Flynn, Anna; McAloon, Catherine; Sugrue, Katie; Fitzgerald, Ricki; Sheridan, Cara; Cowley, Bosco; McAloon, Conor; Kennedy, Emer (Frontiers in Veterinary Science, 2024)
Abstract Despite the fact that pneumonia remains a leading cause of mortality and morbidity in pre-weaned calves relatively little is known regarding the effects of concurrent administration of intranasal pneumonia virus vaccines, particularly in calves with high levels of maternally derived antibodies. The objective of this study was to use a cohort of 40 dairy and dairy-beef female and male calves (27 females and 13 males) to determine serological responses to concurrent administration, at three weeks of age (22 ± 4.85 days), of two commercially available intranasal (IN) vaccines for the viruses; Bovine Respiratory Syncytial Virus (BRSV), Bovine Herpes Virus 1 (BoHV-1), and Parainfluenza-3-virus (PI3-V). The study groupings were; i) Bovilis IBR Marker Live only® (IO), ii) Bovilis INtranasal RSP Live® only (RPO), iii) Concurrent vaccination with Bovilis IBR Marker Live® & Bovilis Intranasal RSP Live® (CV) and iv) a control group of non-vaccinated calves (CONT). The calves’ serological response post IN vaccination, clinical health scores, rectal temperatures, and weights were measured. Data was analyzed in SAS using mixed models and logistic regression. The CV calves had an average daily weight gain (ADG) of 0.74 (± 0.02) kg, which was similar to CONT (0.77 ± 0.02 kg). Despite no significant differences in antibody levels between study groups three weeks post-IN, following administration of subsequent parenteral injections in the form of Bovilis Bovipast RSP®(antigens; inactivated Bovine Respiratory Syncytial virus, inactivated Parainfluenza-3-Virus, inactivated Mannheimia haemolytica) and Bovilis IBR Marker Live®. BRSV and PI3-V antibody levels rose in both the CV, and RPO study groups. Concurrent vaccination resulted in no increase in fever, and no difference in health scores when compared to CONT.